Teachers’ and Learners’ Beliefs About Pronunciation Instruction in Tertiary English as a Foreign Language Education - Nguyen, Loc Tan; Hung, Bui Phu; Duong, Uyen Thi Thuy; Le, Tu Thanh (Frontiers in Psychology, 2021)
Recent studies have sought to describe and understand ESL/EFL teachers’ pronunciation teaching practices in different contexts, but much less research has examined how teachers and learners perceive pronunciation instruction at the university level. The qualitative study reported in this paper extends this line of research by investigating the perceptions of teachers and learners with regard to pronunciation instruction in tertiary EFL education in Vietnam. Data were collected from individual semi-structured interviews with six EFL teachers and focus group interviews with 24 students (four students per group) at a Vietnamese university. The study adopted a content-based approach to qualitative data analysis. The findings show that both the teachers and students considered pronunciation instruction an important component in tertiary EFL programmes which deserves explicit and systematic delivery. The findings suggest that both groups of participants believed communicative pronunciation teaching to have the potential to improve learners’ pronunciation and facilitate their general communicative purposes.